Clinical and prognostic impact of chronotropic incompetence in patients with hypertrophic cardiomyopathy. (15th November 2018) - Magri, Damiano; Agostoni, Piergiuseppe; Sinagra, Gianfranco; Re, Federica; Correale, Michele; Limongelli, Giuseppe; Zachara, Elisabetta; Mastromarino, Vittoria; Santolamazza, Caterina; Casenghi, Matteo; Pacileo, Giuseppe; Valente, Fabio; et al.
Abstract: Background: A blunted heart rate (HR) response is associated with an impaired peak oxygen uptake (pVO2 ), a powerful outcome predictor in hypertrophic cardiomyopathy (HCM). The present multicenter study sought to determine the prognostic role for exercise-induced HR response in HCM. Methods: A total of 681 consecutive HCM outpatients on optimized treatment were recruited. The heart failure (HF) end-point was death due to HF, cardiac transplantation, NYHA III-IV class progression, HF worsening leading to hospitalization and severe functional deterioration leading to septal reduction. The sudden cardiac death (SCD) end-point included SCD, aborted SCD and appropriate implantable cardioverter defibrillator discharges. Results: During a median follow-up of 4.2 years (25–75th centile: 3.9–5.2), 81 patients reached the HF and 23 the SCD end-point. Covariates with independent effects on the HF end-point were left atrial diameter, left ventricular ejection fraction, maximal left ventricular outflow tract gradient and exercise cardiac power (ECP = pVO2 ∗systolic blood pressure) (C-Index = 0.807) whereas the HCM Risk-SCD score and the ECP remained associated with the SCD end-point (C-Index = 0.674). When the VO2 -derived variables were not pursued, peak HR (pHR) re-entered in the multivariate HF model (C-Index = 0.777) and, marginally, in the SCD model (C-index = 0.656). A pHR = 70% of the maximum predicted resulted as the best cut-off value in predicting the HF-related events. Conclusions: The cardiopulmonary exercise test is pivotal in the HCM management, however the pHR remains a meaningful alternative parameter. A pHR < 70% identified a HCM population at high risk of HF-related events, thus calling for a reappraisal of the chronotropic incompetence threshold in HCM. Highlights: Peak VO2 is an emerging outcome predictor in hypertrophic cardiomyopathy. The exercise-induced HR response contributes physiologically to the peak VO2 . The clinical and prognostic role of chronotropic incompetence in HCM is still debated. A blunted exercise-induced HR response is associated to an increased HF and SCD risk. A peak HR < 70% of the maximum age-predicted identifies those HCM patients at high risk.